Design and optimization of a rectangular microstrip patch antenna for dual-band 2.45 GHz/ 5.8 GHz RFID application - El Mattar, Sara; Baghdad, Abdennaceur (Institute of Advanced Engineering and Science, 2022)
This paper introduces a new rectangular slot antenna structure based on a simple rectangular shape with two symmetrical rectangular slots on the radiated element. The aim of this work is to design an antenna and enhance it to function in the band (2.45 GHz and 5.8 GHz). We formulated the dimensions of the antenna using the transmission line model of the analytical methods and then we optimized these parameters using the CST Microwave Studio simulator. We made changes to two important parameters in our design: the position and width of the slots when the other parameters are kept constant. The resulting antenna provides good adaptation, high gain that achieves 5.96 dBi at 2.45 GHz and 6.491 dBi at 5.8 GHz, good return loss values of -49.859 dB and -34.303 dB for the lower and upper operating frequencies respectively. For radio frequency identification (RFID) implementations, the proposed antenna is ideal, and its main advantage is that it has high gain and is simple to design and fabricate.